Steering kernel-based guided image filter for single image dehazing - Yadav S.K.; Sarawadekar K. (My University, 2025)
The guided image filter (GIF) technique is used for haze removal. It reduces the gradient reversal artifact as well as preserves the edge information precisely in smooth (flat) region only. However, it fails to avoid halo artifact and edge-smoothing effect in sharp regions. So, to mitigate this problem, we propose an adaptive haze removal algorithm using a steering kernel-based guided image filter (SKGIF). Steering kernel determines the edge-direction in guidance image more adequately. The edge-direction is an essential feature of guidance image, and it helps to determine more edge-preserving information in flat as well as sharp regions. Experimental outcomes on different hazy images prove the effectiveness of the proposed algorithm. © 2020 IEEE.